Healthcare Providers' Knowledge and Current Practice of Pain Assessment and Management: How Much Progress Have We Made? - Nuseir, Khawla (Pain Res Manag, 2016)
Context. Despite improvement in pain management and availability of clinical treatment guidelines, patients in Jordan are still suffering from pain. Negative consequences of undertreated pain are being recognized as a reason for further illnesses and poor quality of life. Healthcare providers (HCPs) are responsible for relieving pain of their patients. Objective. To evaluate the knowledge and attitudes of HCPs toward pain management in Jordan. Methods. A 16-item questionnaire with agree or disagree options was given to 662 HCPs in seven hospitals in Jordan who volunteered to participate in the study. Following data collection, the responses were coded and entered into SPSS. Results. There was a statistically significant difference (p < 0.004) in percentage scores between physicians (36%) and pharmacists (36%) versus nurses (24%). The level of knowledge was the best among physicians, followed by pharmacists specifically in the area of cancer pain management. Nurses scored the lowest for knowledge of pain assessment and management among HCPs. However, HCPs overall scores indicated insufficient knowledge specifically in relation to pain assessment and management among children.